Preparation of Pineapple (Ananas comosus) Candy Using Osmotic Dehydration Combined With Solar Drying (The Agriculturists, 2016)
This study was conducted to develop pineapple candy prepared from fresh pineapple using 40, 50 and 60% sugar solution and then dried in solar drier. Acceptability of the product was also assessed. The thickness of pineapple slices were 0.5 and 1.0 cm. The pineapple slices were dipped into 40, 50 & 60% sugar solutions for overnight and then dried in solar drier. It was found that 0.5 cm thick of pineapple slices dried quickly than 1 cm thick slices. Sensory quality attributes of the prepared pineapple candy were analysed on the basis of colour, flvour, texture and overal acceptability using ANOVA test followed by DMRT test for identification of  the best pineapple candy. Samples having  0.5 cm slice, osmosed in 60 % sugar solution and 0.5 cm slice, osmosed in 50% sugar solution were the preferred samples with respect to quality attributes and ranked as like very much. The samples having 0.5 cm slice, osmosed in 60 % sugar solution  was the most acceptable among candies prepared under the study.The Agriculturists 2015; 13(1) 87-93